The Sequencing of Examination Questions and Its Effects on Student Performance. - Paretta, Robert L.; Chadwick, Lester W.; De Coster, Don T. (The Accounting Review, 1975)
Abstract This article presents a study conducted to analyze the effects of sequencing of questions in accounting examinations on student performance. The preparation of examinations, especially in accounting, requires a great deal of care if they are truly to reflect a student's mastery of the subject. Regardless of how much effort one puts into making up an examination, some students will nevertheless complain that it did not "fairly" measure their knowledge. Unfortunately, too little is known about the sequencing of examination questions and its effects on student performance to be able to say whether this complaint is justified. When examinations consist of questions that are not of equal difficulty, sources in the education literature recommend that they be arranged in order of increasing difficulty. This is considered desirable because it avoids the possibility of weaker students getting discouraged because of their inability to respond to difficult questions early in the test. The study was designed to test this notion involving 306 elementary accounting students enrolled at the University of Delaware, in the College of Business and Economics.